INTERNALISASI NILAI PENDIDIKAN KARAKTER MELAUI SATUA I KARUNA - I Nengah Arimbawa; I Nengah Adi Widana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Education is now a basic need, which is expected to increase a person's life. However, starting in 2020 the world of education experienced a very significant turmoil, this was due to the Covid-19 pandemic. Where initially education was carried out face-to-face/directly, education was carried out in an